Modeling of the impact of biological drugs in the economic burden of severe asthma - S. K. Zyryanov; I. N. Dyakov; O. I. Karpov (Izdatelstvo OKI, 2020)
Bronchial asthma (BA) is worldwide lungs' illness, at least 1,5 mln people are on a dispensary in Russia. Non-control severe BA (SBA) can lead to increasing of direct Health Care System expenditures due to very oft en exacerbations (drugs costs, hospitalizations and out-patient cure etc.) as well as to increasing of non-direct costs because temporary and permanent disability can be a result of a disease progression. Treatment of SBA has difficulties, system steroids with their well-known side effects use often as remedy of choice. Biologicals with high efficacy potential and minimal side effects are used in a clinical practice during few last years.Aim: evaluation of a comparative influence of two biologicals - dupilumab and omalizumab - on a calculated SBA burden in the Russian Federation.Materials and methods: Modelling of SBA population size which has needed in biologicals has been prepared based on official statistics and Register of SBA. Direct costs (drugs costs, treatment costs in out-patient departments and in hospitals, visits to doctors etc.) and non-direct costs (payment for temporary and permanent disability, GDP losses) have been modelling and calculated.Results: Estimated BA patient population size in Russia is 6.94 mln, and non-control SBA amount is 69,7 thousand (31.7 thousand patients in economic active age). The current treatment SBA option (w/o biologicals) has expenditures at least 1 447,2 RUR annually (direct and non-direct in total). Biologicals should decrease total expenditures due to high efficacy - for dupilumab total expenditures could be 495,42 mln RUR/year, for omalizumab - 559,81 mln RUR/year for all patients who are needed in these drugs. Omalizumab has higher weighted average estimated cost in compare with dupilumab (1.19 mln RUR/patient/year and 1.01 mln RUR/patient/year accordingly) and expenditures for omalizumab were higher due to less amount of prevention of exacerbations.Conclusion: Expenditures for SBA w/o biologicals are higher in compare with biologicals treatment options. Treatment with dupilumab for all patients with non-control SBA could decrease a direct cost on 5,8 %. Dupilumab and omalizumab usage is economically proved in non-control SBA for total cost saving (direct and non-direct).